2019 IEEE PES Innovative Smart Grid Technologies Europe (ISGT-Europe) 2019
DOI: 10.1109/isgteurope.2019.8905500
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Offshore Wind with O&G Platforms with an Energy Storage System

Abstract: Offshore O&G exploration companies are moving to greater depths to access more abundant O&G reservoirs in deeper waters, resulting in higher costs for HVDC power transmission. As such, an integrated system consisting of an offshore floating wind farm and O&G production platforms with a battery energy storage system (BESS) is proposed in this paper. Transient stability results of the proposed system shows a reduction in transient deviation in load power from-19% to +2/-10%, which meets the IEC and NORSOK standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the typical system, the O&G platforms are equipped with 2 x SCGTs (16.4-MW) and standby 1 x SCGTs (8.2-MW), where two SCGTs act as essential generators (EGs) and the other serves as an emergency essential generator (E.EG). The typical OG platforms have a fixed load of around 8.5-MW, as discussed in [11]. The conventional system consists of 1 x 6-MW Siemens (SWT6.0-154) Permanent Magnet Synchronous Generator (PMSG) floating WTGs connected in parallel, which mirrors the Hywind Park configuration in the North Sea [15].…”
Section: A Integrated System For Oil and Gas Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the typical system, the O&G platforms are equipped with 2 x SCGTs (16.4-MW) and standby 1 x SCGTs (8.2-MW), where two SCGTs act as essential generators (EGs) and the other serves as an emergency essential generator (E.EG). The typical OG platforms have a fixed load of around 8.5-MW, as discussed in [11]. The conventional system consists of 1 x 6-MW Siemens (SWT6.0-154) Permanent Magnet Synchronous Generator (PMSG) floating WTGs connected in parallel, which mirrors the Hywind Park configuration in the North Sea [15].…”
Section: A Integrated System For Oil and Gas Platformsmentioning
confidence: 99%
“…This is further driven by the fact that capital expenditure (CapEx) of O&G platforms will be higher if subsea transmission cables are required to connect to the onshore power grid [10]. Battery energy storage system (BESS) has also been proposed to integrate with an offshore floating wind farm and O&G production platforms for load flow analysis without considering voltage and frequency deviation [11]. A subsequent study on transient stability analysis with ETAP on O&G platforms with WTG and 2MW of BESS has shown that the voltage and frequency deviations meet the IEC standards 61892-1 for oil and gas industry [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology of battery energy storage system (BESS) has been decreasing in cost swiftly over the years due to high demand in improving power stability [9]. This is a critical element in transient stability improvement, which has always been the main research focus in the integration of OOR and WTG that is introduced in [10], [11]. Since then, a similar application has been presented in [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the load demand control to follow the wind variations contributes to a lower average rotor speed deviation. Reference [7] proposed a system consisting of an offshore floating wind farm connected to an O&G production platform with a BESS. Due to the incorporation of BESS, one of the gas generators was no longer required resulting in reduced greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%